ID: 20. Issue 4 (April 2016) - Rothschild, M; Vijaykumar, A; Goldenberg, M; Motayar, N; Weber, J; Prince, M; Glueck, CJ; Wang, P
Abstract : Background: In patients hospitalized over a 4 year period for pulmonary embolism (PE), and subsequently found to have familial-acquired thrombophilia, we assessed relationships of thrombophilia with testosterone (TT) and estrogen therapy (ET) anteceding PE. Methods: From 2011 through 2014, 347 patients were hospitalized in Cincinnati Mercy Hospitals with PE. Retrospective chart review was used to document TT or ET anteceding PE in patients subsequently found to have familial or acquired thrombophilia. Results: Preceding hospitalization for PE, of the 154 men and 193 women, 8 men (5% of men) used TT, 24 women (12% of women) used ET (16 birth control pills, 6 hormone replacement therapy, 2 progesterone). Median age in the 8 men was 56 and for the 24 women 38. After excluding 45 women with cancer preceding PE, 24 of 148 (16%) women with PE had used ET, and after excluding 33 men with cancer, 8/121 men (7%) used TT. Of these 8 men, 6 used TT gels, 50 mg/day, and 2 had intra muscular TT 50 mg/week. Of the 8 men, 5 (63%) smoked, 2 had a history of thrombotic events, and 2 had type 2 diabetes. The median number of months from the initiation of TT to development of PE was 7 months. Coagulation evaluations were done in 6 of the 8 men. All 6 had ≥1 thrombophilia; 1 heterozygous for the G20210A prothrombin gene (PTG) mutation, 1 with high factor VIII, 3 with high homocysteine (1 of whom had MTHFR C677T homozygosity), 2 with low protein C, 2 with low protein S, and 2 with low free protein S. Two of 8 men had Klinefelter's syndrome. Of the 24 women, 2 were diabetic, 1 had a history of thrombosis, and 7 (29%) smoked. The median time between initiation of ET and the PE was 18 months. In 18 out of the 24 women, coagulation evaluations were performed. 15 had ≥1 thrombophilia; 4 were factor V Leiden heterozygotes, 1 PTG heterozygote, 2 high Factor VIII, 1 high Factor XI, 2 with the lupus anticoagulant, 3 low protein S, 2 low Free S, 3 low antithrombin III, 3 high anticardiolipin antibodies. Conclusion: After excluding antecedent cancer, 24/148 women (16%) had ET before PE, and TT was taken by 8/121 (7%) men. PE is an important complication of TT in men and ET in women, in part reflecting an interaction between familial and acquired thrombophilia and exogenous hormone use.